Exploring What Teacher's Decision-Making in Designing Mathematical Assignments?: Case Studies in Beginner - Taufiq Taufiq; Mega Teguh Budiarto; Tatag Yuli Eko Siswono (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research uses the M-Four theory to investigate how teachers design mathematical tasks based on contextual problems. Method: The research involves a case study approach, utilizing in-depth observations, interviews, and Mathematical Task Design Sheets (MTDS) for data collection. This study involved one Beginner Teacher (BT) (age 35) participating who was selected based on teacher experiences. Through observation results, a BT who consistently assigns contextual math problems is selected for further analysis. Results: The study's findings reveal that BT tends to produce contextual assignments that primarily focus on the context presented in the textbook, with minimal additions or adjustments based on real-life situations experienced by students. This research contributes to the existing literature on problem-based learning and task design by examining the perspectives of BT. It provides insights for teacher professional development programs and curriculum design. Novelty: The novelty of this research lies in its exploration of how BT designs mathematical tasks based on contextual problems using the M-Four theory.